Effect of Photobiomodulation on Repairing Pressure Ulcers in Adult and Elderly Patients: A Systematic Review. (10th November 2019) - Petz, Francislene de Fatima Cordeiro; Félix, Jorge Vinicius Cestari; Roehrs, Hellen; Pott, Franciele Soares; Stocco, Janislei Giseli Dorociaki; Marcos, Rodrigo Labat; Meier, Marineli Joaquim
Abstract: Evaluation of photobiomodulation therapy (PBMT) in the treatment of pressure ulcers in adults and the elderly. Systematic review, based on the recommendations of the handbook, proposed by Cochrane. The search was carried out in databases, records of randomized clinical trials, list of references cited in the selected articles, as well as a manual search in meetings and specialized journals. A total of 1342 studies were identified, 18 were preselected and 5 were included in this review. Clinical heterogeneity of the participants was observed, in addition to variation in the laser parameters and predominance of studies of low methodological quality. PBMT with the use of laser (658 nm; 4 J cm −2 ;50 mw) showed complete wound healing ( P < 0.001) when compared to lasers (990 nm and 808 nm). However, there was no statistically significant difference in relation to time to complete wound healing and in area reduction compared to standard care. PBMT in the infrared wavelength showed efficacy in the healing of the pressure ulcer, similar to the standard care presented in the different studies. PBMT (658 nm) was effective in promoting healing when compared to standard care. Laser can be a therapy of choice in the treatment of pressure ulcers, since no evidence has been found to refute its clinical application. Abstract : Pressure ulcers are highly prevalent among adult and elderly patients where risk factors vary. In addition to guidelines to the conventional treatment, some auxiliary therapies such as photobiomodulation have shown promising results in wound healing. In this systematic review, only 5 papers were selected according to the eligibility criteria of this research. It was observed that PBMT red wavelength, similar to standard care, promoted tissue repair with a reduced lesion area.